Does chronic pain hinder physical activity among older adults with type 2 diabetes? - Nanna Wackström; Anne M. Koponen; Sakari Suominen; Ina M. Tarkka; Nina Simonsen (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Background:Physical activity (PA) is a key component in management of type 2 diabetes (T2D). Pain might be a barrier to PA especially among older adults with T2D, but surprisingly few studies have investigated the association between chronic pain and PA. Our aim was to evaluate the prevalence of chronic pain among older adults with T2D and to examine the association between chronic pain and PA while taking important life-contextual factors into account.
Methods:Data of this register-based, cross-sectional study were collected in a survey among adults with T2D (n=2866). In the current study, only respondents aged 65-75 years were included (response rate 63%,n=1386). Data were analysed by means of descriptive statistics and multivariate logistic regression analysis.
Results:In total, 64% reported chronic pain. In specific groups, e.g. women and those who were obese, the prevalence was even higher. Among respondents experiencing chronic pain, frequent pain among women and severe pain among both genders were independently associated with decreased likelihood of being physically active. Moreover, the likelihood of being physically active decreased with higher age and BMI, whereas it increased with higher autonomous motivation and feelings of energy. Among physically active respondents suffering from chronic pain, neither intensity nor frequency of pain explained engagement in exercise (as compared with incidental PA). Instead, men were more likely to exercise regularly as were those with good perceived health and higher autonomous motivation.
Conclusions:The prevalence of chronic pain is high among older adults with T2D. This study shows that among those suffering from chronic pain, severe pain is independently and inversely associated with being physically active, as is frequent pain, but only among women. Moreover, the findings show the importance of autonomous motivation and health variables for both incidental PA and exercise among older adults with T2D experiencing chronic pain.